Automated diagnosis of damages in ceilings by a portable device. (2017) - Collini, L.; Foresti, R.; Garziera, R.
Abstract: An automated diagnosis method for the health monitoring of ceilings in civil structures is here presented and discussed. The innovative, portable instrumentation here presented is capable of automatically tapping a small area of the ceiling by the shot of a controlled-energy pin and of simultaneously measuring the out of plane vibration of this area. The comparison of different vibrational behavior of tested ceiling areas can indicate presence of sub-superficial detachments that are potentially dangerous for persons, since cause of sudden collapses.